KORELASI INDIKATOR PHBS DI TINGKAT RUMAH TANGGA DENGAN KEJADIAN DIARE - Diana Rahmawati; Dwi Helynarti Syurandhari; Arief Fardiansyah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Diarrhea is a disease characterized by defecation more than three times a day with changes in the form and consistency of loose stools which may be accompanied by vomiting or bloody stools. The purpose of this study was to determine the relationship between environmental indicators on the household PHBS concept, namely the use of clean water, CPTS behavior and the use of healthy latrines with the incidence of diarrhea in RW 02 Blandongan Village, Pasuruan City. The research method is a correlative descriptive using a contingent coefficient test to determine the correlation between variables. Retrieval of data using a questionnaire with a crosssectional approach. The number of samples is 148 respondents with random sampling. Based on the descriptive analysis, it was found that 17 families experienced diarrhea. Based on the correlation analysis, it is known that the strength of the relationship between the independent variables and the incidence of diarrhea is the dependent variable, namely the use of clean water has no significant correlation with very weak relationship strength (C = 0.049), CTPS behavior has a significant correlation with very moderate relationship strength (C = 0.424) and the use of healthy latrines did not have a significant correlation with very weak relationship strength (C = 0.014). The conclusion of this study is that the behavior of washing hands with soap and running water (CTPS) has a significant correlation with the incidence of diarrhea. While the use of clean water and the use of healthy latrines have no significant relationship with the incidence of diarrhea in RW 02 Blandongan Village, Pasuruan City